Primary structure and functional expression of the human cardiac tetrodotoxin-insensitive voltage-dependent sodium channel. - Gellens, M E (1992)
The principal voltage-sensitive sodium channel from human heart has been cloned, sequenced, and functionally expressed. The cDNA, designated hH1, encodes a 2016-amino acid protein that is homologous to other members of the sodium channel multigene family and bears greater than 90% identity to the tetrodotoxin-insensitive sodium channel characteristic of rat heart and of immature and denervated rat skeletal muscle. Northern blot analysis demonstrates an approximately 9.0-kilobase transcript expressed in human atrial and ventricular cardiac muscle but not in adult skeletal muscle, brain, myometrium, liver, or spleen. When expressed in Xenopus oocytes, hH1 exhibits rapid activation and inactivation kinetics similar to native cardiac sodium channels. The single channel conductance of hH1 to sodium ions is about twice that of the homologous rat channel and hH1 is more resistant to block by tetrodotoxin (IC50 = 5.7 microM). hH1 is also resistant to mu-conotoxin but sensitive to block by therapeutic concentrations of lidocaine in a use-dependent manner.